Strategic analysis of the migration of talent within the European Union - Ferrer-Serrano, Marta; Latorre-Martínez, María Pilar; Hermoso-Traba, Ramón (Acciones e Investigaciones Sociales, 2019)
Introduction: this article focuses primarily on highlighting the importance of the mobility of human resources, especially talent, within the European Union. This is approached from the premise that the phenomenon is beco- ming ever more prevalent in today’s world due to the presence of a deep- rooted sense of competition. Methodology: a large part of the article is devoted to the collection of data from two different perspectives: economics and education. The quantitative data is then analysed using statistical correlations (Pearson’s coefficient). Results: there are a number of findings that draw attention to the relation- ship between the variables forming the object of this study, particularly in the case where any significant statistical correlations emerge. Conclusion: the relationship between the macroeconomic and educatio- nal variables selected in this study throw up relevant information that reveals the general situation of the mobility of EU talent, providing a glimpse of the new challenges – both general and individual – that the member states need to tackle.